Strategic Coordination of BP3OKP in Implementing the Papua Cerdas Mission Based on the Papua Development Acceleration Master Plan (RIPPP) - Gosul, Nursandrawali; Bambang Shergi Laksmono (International journal of technology and education research, 2025)
The development of the education sector in Papua Province continues to face structural, cultural, and geographical challenges. In response, the Government of Indonesia established the Steering Agency for the Acceleration of Special Autonomy Development in Papua (BP3OKP) as a strategic institution tasked with coordinating development planning under the framework of Special Autonomy. This study aims to analyze the role of BP3OKP in coordinating the planning of the “Papua Cerdas” mission, as outlined in the 2022–2041 Master Plan for the Acceleration of Papua Development (RIPPP). Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and document analysis. The analysis applies the Result-Based Management (RBM) framework, particularly the Setting the Vision stage. The findings reveal that BP3OKP plays a pivotal role in aligning national policy directions with local needs through cross-sectoral collaboration involving regional governments, customary institutions, educational foundations, and national ministries. Despite having a strong legal mandate and institutional foundation, challenges remain in inter-agency coordination and the optimal utilization of Special Autonomy Funds for priority education programs. This study recommends strengthening institutional capacity and refining coordination mechanisms as key strategies to accelerate the inclusive and sustainable realization of the “Papua Cerdas” mission.